2022
DOI: 10.3389/fonc.2022.927108
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recovery of Postoperative Pulmonary Function in Patients With Lung Cancer and Influencing Factors

Abstract: Among malignant tumors, lung cancer has the highest morbidity and mortality worldwide. Surgery is the first-line treatment for early-stage lung cancers, and has gradually advanced from conventional open-chest surgery to video-assisted thoracic surgery (VATS). Additionally, increasingly smaller surgical incisions and less surgical trauma have resulted in reduced pulmonary function damage. Previous studies have found that the level of pulmonary function loss and recovery is significantly correlated with postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In this study, we only included patients who underwent VATS surgery, partly because over 95% of lung surgeries in our center were performed using thoracoscopy, and open surgery was more closely associated with patients’ specific conditions. On the other hand, Lung surgery with VATS spares more chest wall muscle, cause less surgical trauma and less respiratory muscle injury, than conventional open-chest surgery, and hence are more conducive to postoperative pulmonary function recovery 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only included patients who underwent VATS surgery, partly because over 95% of lung surgeries in our center were performed using thoracoscopy, and open surgery was more closely associated with patients’ specific conditions. On the other hand, Lung surgery with VATS spares more chest wall muscle, cause less surgical trauma and less respiratory muscle injury, than conventional open-chest surgery, and hence are more conducive to postoperative pulmonary function recovery 30 .…”
Section: Discussionmentioning
confidence: 99%
“…28 The preoperative pulmonary functional status can have a substantial impact on the patient's prognosis and postoperative quality of life. 29 Preoperative pulmonary function training can enhance pulmonary ventilation and reduce pulmonary complications. 30 Polański et al found that patients with anxiety and depression had a significantly lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Third, only 3D-CT and pulmonary function tests, which mainly focus on lung air volume, were performed. In other words, indices such as pulmonary blood flow, oxygen uptake, and symptoms of patients, such as percutaneous oxygen saturation (SpO 2 ), partial pressure of arterial oxygen (PaO 2 ), diffusing capacity of lung for carbon monoxide (DLCO), and the 6-minute walking test ( 22 , 27 , 28 ). Furthermore, in the analysis of volumetric changes before and after surgery, as conducted in this study, where the residual lungs divided into several parts, investigations utilizing imaging techniques for a more detailed local volume analysis that reflects more functional lung volume assessments—such as these reported by previous studies with lung perfusion SPECT/CT, radiologic lung weight, and functional lung volume measurement for example excluding low attenuation area—were not undertaken in our research ( 10 , 11 , 19 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%